Secondary Infections in Patients with Extremely Severe COVID-19 During ECMO Therapy - S. S. Andreev; M. V. Ketskalo; P. O. Narusova; M. A. Lysenko (Общая реаниматология)
Up to 70% of patients hospitalized for COVID-19 need respiratory support, up to 10% need high-flow oxygen therapy, non-invasive and invasive ventilation. However, standard methods of respiratory support are ineffective in 0.4-0.5% of patients. In case of potentially reversible critical refractory respiratory failure that patients may require ECMO. Management of patients with extremely severe COVID-19 associates with numerous clinical challenges, including critical illness, multiple organ dysfunction, blood coagulation disorders, requiring prolonged ICU stay and care, use of multiple pharmacotherapies including immunosuppressive drugs. Pharmacological suppression of immunity is associated with a significant increase in the risk of secondary bacterial and fungal infections. Currently, data on epidemiology of secondary infections in patients with COVID-19 undergoing ECMO is limited.Aim. To study the prevalence and etiology of secondary infections associated with positive blood cultures in patients with extremely severe COVID-19 requiring ECMO.Materials and methods. A single-center retrospective non-interventional epidemiological study including 125 patients with extremely severe COVID-19 treated with ECMO in April 2020 to December 2021.Results. Out of 700 blood culture tests performed in 125 patients during the study, 250 tests were positive confirming bacteremia/fungemia. Isolated pathogens varied depending on the duration of ECMO: gram-positive bacteria (primarily coagulase-negative staphylococci) dominated from the initiation of ECMO support; increased duration of ECMO associated with an increasing the proportion of pathogens common in ICU (Klebsiella pneumoniae and/or Acinetobacter baumannii with extensively drug resistant and pan-drug resistant phenotypes, and vancomycin-resistant Enterococcus faecium). When ECMO lasted more than 7-14 days, opportunistic pathogens (Candida species, Stenotrophomonas maltophilia, Providencia stuartii, non-diphtheria corynebacteria, Burkholderia species and others) prevailed as etiological agents.Conclusion. Longer duration of ECMO resulted in increasing the rates of infectious complications. In patients undergoing ECMO for more than 14 days, the microbiological landscape becomes extremely diverse, which hampers choosing an empirical antimicrobial therapy. Since potential pathogens causing secondary infections in patients during ECMO are difficult to predict, rapid identification of rare opportunistic pathogens and their sensitivity profile, followed by targeted administration of antimicrobials, seems most beneficial.